2008
DOI: 10.1063/1.2909976
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of a nanoporous silica under compressive loading

Abstract: In a compression experiment on a nanoporous silica gel, it is observed that at a high pressure the collapse of nanoporous structure provides a mechanism for plastic deformation, leading to an energy absorption efficiency much higher than that of many conventional protection and damping materials. Even though the network material is brittle, the overall behavior of the silica gel is ductile. After the compression test, the nanopore volume is largely reduced while the variation in nanopore surface area is second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Using a simple failure model they then concluded that pore collapse is due to buckling of the solid edges. Han et al [19] reached a similar conclusion.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Using a simple failure model they then concluded that pore collapse is due to buckling of the solid edges. Han et al [19] reached a similar conclusion.…”
Section: Discussionsupporting
confidence: 56%
“…Lemay et al [9] performed a study on aerogel material using uni-axial loading but they did not study the pore size evolution under these conditions. Han et al [19] studied the effect of uni-axial loading on nanoporous silica material that was fabricated by pelletizing silica particles into monolithic disks with densities of 0.7-1.1 g/mL. They found that the overall behavior of the material was ductile and, like Pirard et al [4], they attributed the plastic deformation to buckling of the pore walls parallel to the external loading.…”
Section: Introductionmentioning
confidence: 98%
“…This is consistent with our previous results that the nanoporous structure is not damaged in such tests because its strength is an order of magnitude higher than the applied peak pressure. 27 In other words, the nanoporous structure is not crushed, and the liquid infiltration is the main working mechanism for energy absorption.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the critical pressure of nanopore collapse is at the level of a few hundreds megapascals. 35 In the pressure range of the current study the nanoporous structure is quite stable.…”
mentioning
confidence: 77%